Peran Gereja Dalam Pastoral Konseling terhadap Masalah Perselingkuhan - Agusta Amelia Sumihe (PT. Giat Konseling Nusantara, 2025)
Infidelity is a phenomenon in social life that ruins the integrity of a marriage. The phenomenon of infidelity not only occur in social life but also occur in Christian family. The facts of infidelity ovcur in Christian family in GMIST Pusirungang Gangga Satu. As a Christian family, this would certainly ruin the image and setting of marriage that God has made. Therefor, the church is called for giving service and fellowmen so that each couples or family can respect and preserve the marriage well. This is what is behind and encourages Author to consider more deeply what is the cause of infidelity and how counseling pastoral care concerns the problem of infidelity in the congregation of GMIST Pusirungang Gangga Satu. This research uses qualitative research methods with a descriptive approach. The results of this research shows that economic factors, old love comes back, couples who don't value marriage and therefore have no fear of cheating become the cause of infidelity. And the church must keep doing the pastoral care continuously not once per day before marriage, but it keep continue, so that every couples get the understanding of the meaning of the right marriage.